Evaluation of the assessment practices of mathematics teachers in the intermediate education stage in the light of the competencies approach - a field study on the middle schools in the state of Mila- - Mouras, Mahbouba; Aimer, Siham (Milev Journal of Research and Studies, 2021)
The current study aimed to reveal the field assessment practices carried out by mathematics teachers in the intermediate education stage to evaluate the students’ work and their school achievements, in the framework of implementing the reforms witnessed by the Algerian educational system since 2003. In order to achieve the objectives of this study, we used the descriptive approach and we relied on the form as a main tool to collect the data. The study sample included 73 mathematics teachers (males and females) randomly selected from among 590 teachers; representing the total number original of mathematics teachers affiliated with the Directorate of Education of the State of Mila during the academic season 2020/2021 AD. The data was processed using the statistical program for social sciences (SPSS22). The results of the study concluded that the level of practicing the methods as well as the stages of achievement evaluation in a continuous and regular manner, in the light of the competency approach is high among mathematics teachers in the intermediate education stage in terms of planning, implementation, evaluation of students’ product.